History and Development of Jazz Music - Tashxodjayev, Botir (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article is devoted to the history of creation and stages of development of jazz music, the emergence of Gospel, Spiritual, Ragtime, Blues, Dixieland jazz styles and their founders are described in detail.